Sensory Sensitivity and Intolerance of Uncertainty Influence Anxiety in Autistic Adults - Normansell-Mossa, Karys M.; Top, D. Nicholas; Russell, Nicholas; Freeston, Mark; Rodgers, Jacqui; South, Mikle (Frontiers in Psychology, 2021)
Several models of anxiety in autistic adults have focused on the role of intolerance of uncertainty which has biological and evolutionary bases, as a cognitive explanation for the high prevalence of anxiety in autism. This framework suggests that all people are born with a healthy level of intolerance of uncertainty, and as we develop, this intolerance is lessened as we learn when situations are safe and begin to understand and manage the uncertainty. This process of learning about managing uncertainty does not happen in the same way in those who are high in autistic traits, which could be the reason for the high levels of anxiety symptoms commonly seen in this population. We examined archival data of 199 non-autistic and 55 autistic adults from prior studies in which we collected self-report measures of autistic traits, intolerance of uncertainty, sensory processing, and anxiety. We conducted two path analyses to examine the role of intolerance of uncertainty in anxiety in autistic adults. The first model tested the idea that intolerance of uncertainty, an evolutionary phenomenon common for all people, could explain some of the cognitive aspects of anxiety in autism. The second model suggests that primary neurodevelopmental differences associated with autistic traits underlie the sensory sensitivity and sensory seeking behaviors, which in turn increase intolerance of uncertainty and subsequent anxiety. We found that the “neurodevelopmental” model had better model fit than the “evolutionary stress” model, suggesting that the neurodevelopmental impact of higher levels of autistic traits could moderate a non-autistic trajectory of learning to manage uncertainty as children develop and understand that uncertainty is common and acceptable.